2021
DOI: 10.3390/molecules26196001
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence of the Bystander Effect after Bleomycin Electrotransfer and Irreversible Electroporation

Abstract: One of current applications of electroporation is electrochemotherapy and electroablation for local cancer treatment. Both of these electroporation modalities share some similarities with radiation therapy, one of which could be the bystander effect. In this study, we aimed to investigate the role of the bystander effect following these electroporation-based treatments. During direct CHO-K1 cell treatment, cells were electroporated using one 100 µs duration square wave electric pulse at 1400 V/cm (for bleomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In a recent study, we demonstrated the presence of the bystander effect after bleomycin electrotransfer in CHO cells [ 37 ]. In the present study, we aimed to build on the previous results and analyze the bystander effect on 4T1 cells after bleomycin electrotransfer and after calcium electroporation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we demonstrated the presence of the bystander effect after bleomycin electrotransfer in CHO cells [ 37 ]. In the present study, we aimed to build on the previous results and analyze the bystander effect on 4T1 cells after bleomycin electrotransfer and after calcium electroporation.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we demonstrated the negative bystander effect on CHO cells after bleomycin electrotransfer and hypothesized that the negative bystander effect could be triggered by a similar mechanism to the bystander effect induced by ionizing irradiation [ 37 , 43 , 44 ]. In this study, we extended analysis of the bystander effect and for the first time showed the presence of bystander effect on 4T1 cells after calcium electroporation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cells which are not in between electrodes can also be affected by PEFs application. This phenomenon is called a “Bystander effect” 33 . To our knowledge, no thorough studies were carried out which characterized molecular changes in cells in close proximity to sub-electroporation threshold electric fields range.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cells which are not in between electrodes can also be affected by PEFs application. This phenomenon is called a "Bystander effect" [34]. To our knowledge, no thorough studies were carried out which characterized molecular changes in cells in close proximity to sub-electroporation threshold electric elds range.…”
Section: Discussionmentioning
confidence: 99%